Sobre Burr C. Brundage, The Phoenix of the Wester World, Quetzalcoatl and the Sky Religion - León-Portilla, Miguel (Estudios de Cultura Náhuatl, 2022)
Reseña sobre Burr C. Brundage, The Phoenix of the Wester World, Quetzalcoatl and the Sky Religion, Norman, University of Oklahoma Press, 1981, XVI + 350.